Establishing Performance Standards and Setting Cut-Scores - Rogers, W. Todd; Ricker, Kathryn L. (Alberta Journal of Educational Research, 2006)
This article serves as an introduction to the following four articles in which four methods for establishing standards and setting cut-scores are presented and evaluated. The purposes, nature, and characteristics of performance standards are first reviewed. This is followed by a brief discussion of the methods for setting cut-scores. Berk’s (1986) criteria for evaluating four of these procedures are then presented and described.